VENTURE CAPITAL INTERNATIONALIZATION: SYNTHESIS AND FUTURE RESEARCH DIRECTIONS. (22nd June 2018) - Devigne, David; Manigart, Sophie; Vanacker, Tom; Mulier, Klaas
Abstract: Research on venture capital (VC) internationalization has expanded rapidly over the last decade. This paper reviews the extant literature on VC internationalization and highlights gaps in our knowledge. We identify three major research streams within this literature, which revolve around the following questions: (1) which VC firms invest across borders and what countries do they target; (2) how do VC firms address liabilities of foreign investing; and (3) what are the real effects of international VC investments? We provide an overview of the contributions in these research streams, discuss the role of public policy, and suggest avenues for future research. Specifically, we call for a deeper understanding of: (1) the functioning and impact of VC firms' modes of internationalization; (2) micro‐level processes such as the functioning and decision making of international investment committees, or the development of international human and social capital; (3) the role of country institutions in VC internationalization and its real effects; and (4) the interplay of international VC with alternative financing sources.